Realitas Sosial dalam Perspektif Pemikiran Islam: Kritik atas Teori Konflik, Pertukaran, dan Fenomenologi menuju Konstruksi Teori Sosial Islam - Sulton Ariwibowo; Nur Ahid; Moh. Safi'il Anam; Mohammad Muksi (JOM, 2026)
This article examines social reality through the lens of Islamic thought by critically engaging with three influential Western social theories: conflict theory, social exchange theory, and phenomenology. While these theories offer important insights into social structures, individual behavior, and subjective experience, they are grounded in epistemological assumptions that differ fundamentally from Islamic perspectives. Using a qualitative and conceptual approach, this study analyzes how Islamic thought critiques, complements, and repositions these theories within a normative–transcendental framework. The analysis shows that Islamic thought shares common concerns with conflict theory regarding social injustice and oppression, yet rejects its materialistic and conflict-centered view of social change. Similarly, social exchange theory is considered limited in its reduction of social relations to rational cost–benefit calculations, overlooking moral intention and spiritual motivation emphasized in Islam. Phenomenology, meanwhile, is acknowledged as a useful methodological approach for understanding lived experience and religious consciousness, but is epistemologically constrained by its suspension of metaphysical truth. This study argues that Islamic thought offers an integrative framework that balances structure, agency, and meaning, while grounding social analysis in ethical values and divine revelation. By positioning Islamic thought as a critical epistemological perspective rather than a mere object of analysis, this article contributes to the development of non-Western and value-based approaches in contemporary social theory.